Efficacy of Amphotericin B at Suboptimal Dose Combined with Voriconazole in a Murine Model of Aspergillus fumigatus Infection with Poor In Vivo Response to the Azole - Sandoval-Denis, Marcelo (American Society for Microbiology, 2013)
The combination of amphotericin B at a suboptimal dose (0.3 mg/kg) with voriconazole has shown efficacy in prolonging survival and reducing tissue burden in a murine model of disseminated infection by an isolate of Aspergillus fumigatus that had showed a poor in vivo response to the azole. The efficacy of the combined treatment was higher than that obtained with amphotericin B at 0.8 mg/kg.